Science, Policy, and Conservation Management for a Critically Endangered Primate in the Atlantic Forest of Brazil - Strier, Karen B.; Melo, Fabiano R.; Mendes, Sérgio L.; Valença-Montenegro, Monica M.; Rylands, Anthony B.; Mittermeier, Russell A.; Jerusalinsky, Leandro (Frontiers in Conservation Science, 2021)
Long-standing concerns about the status of the world’s endangered primates have stimulated significant international efforts, such as the primate action plans published by the Primate Specialist Group of the International Union for Conservation of Nature’s Species Survival Commission. However, national-level action plans that bring together diverse scientific experts, non-governmental organizations, and governmental agencies to focus on improving the status of endangered species are generally rare. Here, we highlight one such case published a decade ago, the Brazilian National Action Plan for the Conservation of Muriquis, which promoted the integration of scientific findings about the behavioral ecology, demography, and genetics of northern muriquis with conservation measures supported by the Brazilian government. This plan provided a holistic framework for the development of an effective national strategy that has contributed to significant advances in research and management applied to the conservation of this Critically Endangered species. We hope that this model for muriquis will stimulate conservationists around the world to pursue integrative national-level sponsorship of action plans on behalf of other endangered species.